A Literature Review on the Use of Discord Application in Education: Contributions and the Developments - Evi Isfiatul Jannah; Sri Wahyuni; Nurul Aini; Amjad Ali Jokhio (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
This research intends to conduct a systematic literature review on the use of Discord application in education. The use of technology, such as learning applications in education today is increasing day by day. One such application used by educators is Discord. While some literature reviews have touched on the topic, there is still much to be explored regarding its use in education. Therefore, this study synthesized the findings on two key aspects, namely contributions and developments on Discord by searching empirical research in databases such as Mendeley.com, Connected Papers, and Google Scholar. To deeply explore the research article, the researchers utilized the SLR procedure by Petticrew and Roberts (2006), and to guide the reviews, the researchers used PRISMA 2020 by Page et al. (2021). The research findings revealed that many studies explored students' perceptions of Discord's contributions to the class. While most reported positive perceptions, some revealed negative perceptions due to the application's poor network connection. Furthermore, most of the developments were applied in flipped-based classrooms to test out the created learning system. In conclusion, the researchers found that Discord has made numerous educational contributions and created a new virtual environment.